Processing of raw donkey milk by pasteurisation and UV-C to produce freeze-dried milk powders: The effect on protein quality, digestibility and bioactive properties - Tedeschi, Tullia; Aspri, Maria; Loffi, Cecilia; Dellafiora, Luca; Galaverna, Gianni; Papademas, Photis (My University, 2023)
Non-thermal processing of milk has been considered over the past decade as an alternative or adjunct to thermal processes. UV-C radiation in combination with turbulent flow of opaque liquids seems to be a promising non-thermal method for the reduction of bacterial populations in milk. Apart from confirming the efficacy of UV-C in destroying pathogens and spoilage bacteria, there is a need for assessment of the quality characteristics of the end-product and especially in added-value dairy products where bioactivity of constituents should be preserved during processing. Under this context, freeze-dried donkey milk powder processing by UV-C was studied and the effect on protein quality, digestibility and bioactive properties were assessed. Results show that UV-C treatment retains the protein's quality characteristics highly comparable to the not-treated milk (i.e. raw) rather than the pasteurized milk where some deterioration (i.e. lower bioactivities) was detected.
Keywords: Donkey milk; Bioactivity; Non-thermal processing; UV-C; Protein functionality